Culture shock! Hong Kong - Wei, Betty (Times books international, 1998)
What you may have known or heard about Hong Kong is probably out of date. If you are about to live and work there. You will need this new, revised edition of CULTURE SHOCK! to guide you through the changes since Hong Kong returned to Chineserule. Betty Wei and Elizabeth Li give you the history, describe the people and their traditions. explain the workings of key institutions, and offer clues to the way Hong Kong Chinese deal among themselves and with `foreign devils'' like yourself.